ANALISIS ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN TARIF KAMAR PADA HOTEL GRAND BOUGENVILLE KOTA BENGKULU - Ida Ayu Made Er Meytha Gayatri; Indri Windasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The aim of this study is to determine activity-based costing system in the determination of room rates on Grand Bougenville Hotel of Bengkulu City. Data collection method in this study used is documentation and interview. The method of analysis used is descriptive quantitative, trying to get accurate data in the form of numbers then the data is calculated to get the amount of hotel room rate. There is a difference between room cost which is determined by the management of Grand Bougenville Hotel of Bengkulu City and by applying activity based costing system. The calculation result of room cost by using activity-based costing system, namely for standard rooms of Rp 172.249,- superior of Rp 182.201,- and suite of Rp 331.182,-. Meanwhile, room cost based on the calculations performed by Grand Bougenville Hotel of Bengkulu City known that for the standard room type of Rp 35.599,- superior Rp 31.297 and suite of Rp 57.881. The calculation of the selling price is also different between hotel calculations with the addition of mark up by 25% then the sale price of standard is Rp 240.073 superior is Rp 297.437 and suite is Rp 461.585. There is a lower price difference between the implementation of hotel management price and calculation result by using activity based costing system that is, standard Rp 240.073 superior Rp297.437 and suite Rp 461.585.